Estudio de la demanda eléctrica diversificada en edificios residenciales - Cevallos Salazar, Luis Enrique (2015)
In this work are presented the results of the study of the diversified electric demand for a sample of five new buildings located in the northern part of the city of Quito, which receive electricity from Power Distribution System of Empresa Eléctrica Quito S.A. For each one of the five buildings were made measurements of the real parameters of electricity demand using a network analyzer during 12 days. In addition, this work presents a summary of the load and demand studies for each of the buildings. The main results of the measurements are presented through graphs and tables summarizing the most relevant electric parameters to make a comparison between the real values of demand with those used in the original designs approved by the company of electricity. For each building; curves of electrical demand real, maximum demand and time of occurrence for weekdays and weekends, are showed. Also, estimated load factors and diversified demand factors, are included. Conclusions and Recommendations are also presented.